Family Firms and the Market reaction to Dividend News - Elisabete F. Simões Vieira (2012)
This paper provides an analysis of the market reaction to dividend change announcements in listed and family-controlled firms, analysing 390 dividend change announcements in Portugal over the period from 1991 to 2010, using panel data approach. Family firms present a significantly lower proportion of independent directors than non-family firms, which is consistent with the perspective that family members dominate the board of directors and that family shareholders are common in public traded firms. The results show no evidence of a significant market reaction to dividend change announcements, providing no evidence in support of the dividend signalling hypothesis in the context of the family firms. This conclusion is in accordance with previous studies, which do not distinguish between family and non-family firms. Empirical results demonstrate that family firms present lower payouts than their nonfamily counterparts, giving some support to the expropriation hypothesis. It might be an indication that families expropriate the wealth of shareholders through lower dividends. This result is also consistent with the clientele theory of dividends.